-(12-t)+(2t-4)=

Simple and best practice solution for -(12-t)+(2t-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(12-t)+(2t-4)= equation:


Simplifying
-1(12 + -1t) + (2t + -4) = 0
(12 * -1 + -1t * -1) + (2t + -4) = 0
(-12 + 1t) + (2t + -4) = 0

Reorder the terms:
-12 + 1t + (-4 + 2t) = 0

Remove parenthesis around (-4 + 2t)
-12 + 1t + -4 + 2t = 0

Reorder the terms:
-12 + -4 + 1t + 2t = 0

Combine like terms: -12 + -4 = -16
-16 + 1t + 2t = 0

Combine like terms: 1t + 2t = 3t
-16 + 3t = 0

Solving
-16 + 3t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 3t = 0 + 16

Combine like terms: -16 + 16 = 0
0 + 3t = 0 + 16
3t = 0 + 16

Combine like terms: 0 + 16 = 16
3t = 16

Divide each side by '3'.
t = 5.333333333

Simplifying
t = 5.333333333

See similar equations:

| 17*v/v=7 | | 13/21=x/147 | | 6(x+9)=60 | | 1+2r-r=11+3r | | 12*c=156 | | 4y=-6+4x | | 1+1+5x-8=5x+x | | 90=(x-2)(y-1.5) | | 12/5=x/45 | | (4i)(-8+8i)= | | 5.3x=4.1x+5.76 | | 2.5h+.5(h-1)=-12.5 | | 5x-9=-3x+12+5x | | 7/12=x60 | | 1/8x-9=17 | | 3x+6=8x-49 | | 2x-3(5-3x)=7x+3 | | .3+.2(g+7)=1.5 | | -0.005q^2+2.5q=300 | | 11*y=77 | | 3x+6=10x+3 | | Hg(x)=2g(x) | | (5x-1)/x=1 | | -40(-28/3) | | .1(f-7)+.05f=.8 | | -(x+3)=2+7 | | log32b=-1/4 | | 42=3w-9 | | 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 |

Equations solver categories